Platelet distribution width (PDW) data of patients with nasal polyposis: is it important for clinical severity? - Hamdi Kepekçi, Ahmet; Dizdar, Gökalp; Bestemi Kepekçi, Ali (ENT Updates, 2017)
Objective: The purpose of the present study was to investigate whether high platelet distribution width (PDW) levels correlated with nasal polyps or not. Methods: The study was performed retrospectively in 99 patients who underwent endoscopic sinus surgery for nasal polyposis. Data were collected from the routine preoperative hemograms of the patients. The study group was compared with an age- and sex-matched control group including 150 healthy subjects. The Mann-Whitney U test was used to compare the results of the two groups. Results: The PDW level for the study group was 14.49±2.08, while for the control group it was 13.76±2.14. The PDW levels of the study group were higher than those of the control group, and this difference was statistically significant (p<0.05). Conclusion: The rise of the PDW levels in patients with nasal polyposis should be investigated for the diagnostic value, and the rise of PDW levels in patients with nasal polyposis may be used for its diagnostic evaluation.